Bronchoalveolar Lavage Fluid IFN-γ+ Th17 Cells and Regulatory T Cells in Pulmonary Sarcoidosis - Anders Tøndell; Torolf Moen; Magne Børset; Øyvind Salvesen; Anne Dorthea Rø; Malcolm Sue-Chu (Mediators of Inflammation)
In sarcoidosis, increased Th17 cell fractions have been reported in bronchoalveolar lavage fluid, and elevated numbers of Th17 cells producing IFN-γ have been observed in peripheral blood. The balance between Th1, Th17, and FoxP3+ CD4+ T cell subsets in sarcoidosis remains unclear. Bronchoalveolar lavage fluid cells, from 30 patients with sarcoidosis, 18 patients with other diffuse parenchymal lung diseases, and 15 healthy controls, were investigated with flow cytometry for intracellular expression of FoxP3. In a subset of the patients, expression of the cytokines IL17A and IFN-γ was investigated. The fractions of FoxP3+ CD4+ T cells and Th17 cells were both lower in sarcoidosis compared to controls (P=0.017 and P=0.011, resp.). The proportion of Th17 cells positive for IFN-γ was greater in sarcoidosis than controls (median 72.4% versus 31%, P=0.0005) and increased with radiologic stage (N=23, rho=0.45, and P=0.03). IFN-γ+ Th17 cells were highly correlated with Th1 cells (N=23, rho=0.64, and P=0.001), and the ratio of IFN-γ+ Th17/FoxP3+ CD4+ T cells was prominently increased in sarcoidosis. IFN-γ+ Th17 cells may represent a pathogenic subset of Th17 cells, yet their expression of IFN-γ could be a consequence of a Th1-polarized cytokine milieu. Our results indicate a possible immune cell imbalance in sarcoidosis.